2015
DOI: 10.15291/libellarium.v7i1.202
|View full text |Cite
|
Sign up to set email alerts
|

Students' information behaviour and the role of academic library

Abstract: In this paper the author presented the results of some of the available studies of students' information seeking behaviour conducted in different countries. The aim of these studies was to identify information needs, sources, and types of library use by the university students from various disciplinary fields. According to the results, the majority of the respondents needed the information for academic purposes (such as papers, assignments or examinations), frequently using information sources like books, jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
(13 reference statements)
0
5
0
1
Order By: Relevance
“…This paper explores academic chemists' practices and feelings when seeking, evaluating, and managing when negotiating information seeking choices (Al-Muomen, Morris, and Maynard 2012;Kayongo and Helm 2010;Korobili, Malliari and Zapounidou 2011;Zhang 2017). Recent studies found that millennials' information seeking behaviors may be problematic, resulting in new or naïve researchers moving away from subject specific resources and towards Google and similar digital tools (Lacovic 2015;Lo and Chu 2015;Salisbury, Gupta, and Kumar 2006;Taylor 2012;Walter and Pennavaria 2015;Zass 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This paper explores academic chemists' practices and feelings when seeking, evaluating, and managing when negotiating information seeking choices (Al-Muomen, Morris, and Maynard 2012;Kayongo and Helm 2010;Korobili, Malliari and Zapounidou 2011;Zhang 2017). Recent studies found that millennials' information seeking behaviors may be problematic, resulting in new or naïve researchers moving away from subject specific resources and towards Google and similar digital tools (Lacovic 2015;Lo and Chu 2015;Salisbury, Gupta, and Kumar 2006;Taylor 2012;Walter and Pennavaria 2015;Zass 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Students use wide range of information sources for accomplishing academic task. Journal articles, newspapers/magazines, encyclopaedias, dictionaries and text books are the most heavily used information sources amongst them (Arshad et al , 2016; Baro et al , 2010; Lacović, 2015; Kakai et al , 2004). On the contrary, they use Internet/electronic media for their project work and other leisure activities (Jafre Zainol Abidin et al , 2011).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…kaynaklar yerine interneti tercih etmektedir. Buna ek olarak, birçok üniversite öğrencisi sınavlara hazırlanma ve akademik görevlerini gerçekleştirme aşamasında Google'da arama yapmayı, sanal kütüphanelerde gezinmeyi ve elektronik kaynakları kullanmayı tercih etmektedir (Emeka ve Nyeche, 2016;Lacović, 2015;Mason, Boldrin ve Ariasi, 2010;Tseng, Liang ve Tsai, 2014;Weber, Becker ve Hillmert, 2018). Çevrimiçi ortamlarda; erişilebilirlik, kullanım kolaylığı, bilgiyi arama sürecinde daha az zaman harcama gibi faktörler, öğrencilerin bilgi ediniminde web tabanlı ortamları kullanmasında etkili olmaktadır (Alshahrani, Ahmed ve Ward, 2017;Yılmaz ve Çakmak, 2016).…”
Section: Introductionunclassified